EPR study of interlayer interaction in Gd2O3/Fe nanostructure - A. M. Kasumov; A. I. Dmitriev; Yu. M. Bataiev; M. M. Bataiev; V. M. Karavaeva; K. A. Korotkov; A. I. Ievtushenko (Хімія, фізика та технологія поверхні)
In this work, a nanoscale structure consisting of contacting layers of a metal of the iron subgroup and a rare earth metal oxide (REM) is considered. Such nanostructures have an interesting feature, which is that as a result of the contact of these layers, an increase in the galvanomagnetic, magneto-optical and kinetic properties of ferromagnetic metals are observed. Presumably, the enhancement is due to an increase in the magnetization of these metals, caused by the exchange f - d interaction between the unfilled f- and d-electron shells of the atoms that make up the contacting layers. The aim of this work is to find the possibility of such f - d exchange interaction by the EPR method.